Efektivitas Rekomendasi Psikolog dan Komisi Perlindungan Anak Daerah dalam Putusan Dispensasi Nikah di Pengadilan Agama Wonosobo Perspektif Hukum Islam - anwari, Alam Ridwan; Muhammad Mustahal; Waluyo Sudarmaji (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the effectiveness of recommendations from psychologists and the Regional Child Protection Commission (KPAD) in marriage dispensation cases at the Wonosobo Religious Court from an Islamic law perspective. Marriage dispensation for children under the legal age remains a significant issue in Indonesia, requiring careful consideration of children's rights and best interests. This research aims to analyze the implementation of psychologist and KPAD recommendations in judges' decisions, evaluate their effectiveness in protecting children's interests, and examine their compatibility with Islamic law principles. Using a normative-empirical legal research method with a case study approach, data were collected through document analysis, interviews with judges, psychologists, KPAD officials, and direct observation at the Wonosobo Religious Court. The findings reveal that psychologist and KPAD recommendations are considered by judges but are not the sole determining factor in decisions. Effectiveness is constrained by limited resources, varying recommendation quality, and the dominance of urgent pregnancy considerations. From an Islamic law perspective, these recommendations align with the principles of maslahah (public interest) and protection of offspring (hifz al-nasl), though their implementation requires strengthening. The study recommends enhancing collaboration among institutions, improving the quality of psychological assessments, and developing more comprehensive guidelines that integrate Islamic law principles with child protection